Social attention among students of the psychological counseling department a comparative study (Journal of the College of Basic Education, 2024)
University students are considered one of the most important groups and have an effective role in developing society if their skills and interests are used in a way that benefits society, as well as providing and implanting the necessary priorities for young people to reduce the reasons or prevent their tendency towards interests that harm and corrupt society, as well as encouraging them and embracing their interests to develop them to build a society. Classy and conscious.The current research aims to identifyIdentifying social interest among male and female students of the Counseling Department in picturesGeneralThe significance of the differences in social interest between males and femalesTo achieve the objectives of the current research, the researcher built a scale (social interest among students of the Department of Psychological Counseling). The scale consists of (26) items based on Adler’s theory. The researcher extracted standard statistics and the correlation coefficient of each item with the total score of the scale, as well as apparent validity, construct and reliability, and that all processes The standard showed that it measures the variable, and the latest results showed that the research sample, students of the guidance department, have a social interest, as well as according to the significance of the differences between males.For females, the results showed in favor of males.In light of the results that emerged, the researcher presented a set of conclusions and recommendationsAnd suggestions for future research